Personality-Related Determinants of Physical Activity Among Polish and Spanish Physical Education Students - Gacek, Maria; Kosiba, Grażyna; Wojtowicz, Agnieszka; López Sánchez, Guillermo F.; Szalewski, Jacek (Frontiers in Psychology, 2022)
We aimed to analyse personality-related determinants of physical activity among Polish and Spanish physical education students. The study was conducted among 219 Polish and 280 Spanish physical education students, using the International Physical Activity Questionnaire (IPAQ) and the NEO-FFI Personality Inventory. Polish and Spanish physical education students obtained the highest results for the extroversion category and the lowest in the area of neuroticism. The level of total physical activity for all students was 8,697.21 METs. Among Polish and Spanish physical education students, the level of total, vigorous and moderate physical activity increased along with the increase in extraversion, while a decrease occurred along with the increase in neuroticism. The level of each domain of physical activity also increased in line with the intensification of student conscientiousness. In moderation analyses, it was shown that the students’ home country may be considered a moderator of the relationship between conscientiousness as well as total exercise in such a way that physical activity increased along with the increase in conscientiousness only among the Polish students. In addition, the country is a moderator of the correlation between moderate physical activity and neuroticism (p=0.031), openness (p=0.049) and conscientiousness (p=0.019), with moderate activity only decreasing among Polish students, and increasing along with the increase in openness and conscientiousness. Positive correlations between physical activity, extraversion and conscientiousness, as well as negative ones with neuroticism, were demonstrated among Polish and Spanish students, and also the moderating impact of the country on the correlation between personality-related dimensions and physical activity.